The effect of antioneoplastic agents on the periodontium: a narrative literature review (Research, Society and Development, 2022)
Objective: The aim of this study is to describe a narrative review about the effects of chemotherapeutics agents on periodontium and emphasize the clinical importance of dentists during multidisciplinary therapy in cancer patients. Methods: A exploratory research process was performed in the electronic databases Pubmed/Medline, Embase, Scopus and Scielo, using search terms: “chemotherapy and periodontitis”, “chemotherapy and gingivitis” and “chemotherapy and periodontal disease”, and it was considered articles published until june 2022. Results and discussion: Chemotherapeutic agents do no act on specific cells, they affect rapidly proliferating cells and cause cytotoxicity to connective tissue cells. Therefore, chemotherapeutic agents causes destruction of the junctional epithelium and exacerbates the inflammatory process of the gingival connective tissue. Once periodontitis that occurs by the interaction between bacterial plaque and the host is located, chemotherapeutic agents aggravates its progression. In addition, chemotherapy drugs can affect periodontal tissues indirectly by xerostomia and increasing the amount of bacteria in the mouth. Periodontal diseases are risk factors for systemic diseases such as: cardiovascular diseases, respiratory diseases, diabetes, Alzheimer's disease and adverse pregnancy outcomes and it is up to the dentist of multidisciplinary team to monitor and identify possible risks in the oral treatment of cancer patients. Within the limits of the this literature review, it can be concluded that periodontal tissues are harmzed by chemotherapy and prevention measures or forms of treatment must be taken into account by the dentists of the multidisciplinary oncology team.